KEMAMPUAN BERMAIN DRAMA SISWA KELAS VIIIA SMP NEGERI 19 KOTA JAMBI - Wulandari, Okky; Karim, Maizar; Larlen, Larlen (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The research objective was to describe the ability of aspects of pronunciation, intonation, expression, kinesik, and appreciation. The benefits of this research are useful as input for teachers who teach Indonesian subjects, especially teachers in SMPN 19 Jambi City. Data obtained using quantitative descriptive method implemented in January 2014. Data were obtained by observing the appearance of the drama played by students with attention to several aspects namely: pronunciation, intonation, expression, kinesik, and appreciation. Based on research results is the ability VIIIA grade students in the drama category to play well with an average of 72.98. In the aspect of pronunciation ability of students in the drama category to play well with an average of 15.97. Intonation aspects of students’ ability to play both drama category with an average of 76.4. Mimic aspects of students’ ability to play well with the drama category average of 75.35. Kinesik aspects of students’ ability to play with enough drama category average of 73.97. While the appreciation of aspects of students’ ability to play enough drama category with an average of 75. The results of the study suggested that teachers, especially Indonesian teachers have a container as a child’s talents to be more focused and honed to a better direction again.